2017
DOI: 10.1530/joe-17-6209x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor-κB and advanced glycation end-products expression in lacrimal glands of aging rats

Abstract: The authors and journal apologise for errors in the above paper, which appeared in volume 187 part 1, pages 159-166. The errors relate to: (1) the age of the control rats, which was incorrectly reported on page 160; and (2) the publication of Figure 1A, 2A and 3A which were also published as Figure 3a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This protein drives vesicular docking and apical membrane fusion and it can also play a role in de termining vesicular size (17) (Figure 1). In previous studies, aging rats had presented with dry eye disease, an insulin-signaling im pairment, oxidative stress, and declines in the parasympathetic control of LG function; this revealed an interesting similarity with DM dry eye (18,19) . Some SNARE and Rab family members were also altered in aged LG; particularly, Rab 3 expression was reduced at both the mRNA and protein levels (20) .…”
Section: Insulin Replacement Restores the Vesicular Secretory Apparatmentioning
confidence: 85%
See 1 more Smart Citation
“…This protein drives vesicular docking and apical membrane fusion and it can also play a role in de termining vesicular size (17) (Figure 1). In previous studies, aging rats had presented with dry eye disease, an insulin-signaling im pairment, oxidative stress, and declines in the parasympathetic control of LG function; this revealed an interesting similarity with DM dry eye (18,19) . Some SNARE and Rab family members were also altered in aged LG; particularly, Rab 3 expression was reduced at both the mRNA and protein levels (20) .…”
Section: Insulin Replacement Restores the Vesicular Secretory Apparatmentioning
confidence: 85%
“…Some SNARE and Rab family members were also altered in aged LG; particularly, Rab 3 expression was reduced at both the mRNA and protein levels (20) . In addition, advanced glycation end pro ducts can accumulate in aged and diabetic rat LGs (7,18) .…”
Section: Insulin Replacement Restores the Vesicular Secretory Apparatmentioning
confidence: 99%
“…An increase in both the number of living cells and cell viability with insulin at 5.0 μg/mL was observed from the third to the ninth day of cultivation, compared with day 0 (seeding), as well as with lower or higher doses of insulin, indicating a key role of insulin in a certain range for the homeostasis and proliferation of LGAC (8,20) . The trend to form clusters after the third day revealed that these cells show polarity, as previously observed (15) .…”
mentioning
confidence: 99%